Preparation method of solid electrolyte coating, composite electrode and application of composite electrode

By using composite matrix and hot pressing technology to form a solid electrolyte coating in semi-solid state batteries, the problem of instability of the surface density of the solid coating is solved, the structural and electrochemical properties of the battery are improved, and the safety is enhanced.

CN119253035APending Publication Date: 2025-01-03SVOLT ENERGY TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411381196.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The density of the solid coating surface of semi-solid state batteries fluctuates greatly, resulting in unstable thickness of the electrode sheet, making it difficult to accurately detect and control, affecting the electrochemical performance and safety of the battery.

Method used

The composite matrix includes a polymer film layer, a semi-solid coating and an adhesive layer, and is bonded to the positive electrode or negative electrode sheet by hot pressing technology, and the polymer film layer is removed to form a solid electrolyte coating to accurately control the surface density.

Benefits of technology

The structural stability and electrochemical performance of the solid electrolyte coating are improved, ensuring the cycling and safety performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005069947830000151
    Figure BDA0005069947830000151
  • Figure BDA0005069947830000161
    Figure BDA0005069947830000161
Patent Text Reader

Abstract

The invention relates to the technical field of batteries, in particular to a preparation method of a solid electrolyte coating, a composite electrode and application of the composite electrode. The preparation method of the solid electrolyte coating comprises the steps that a composite matrix is obtained, and the composite matrix comprises a polymer film layer, a semi-solid coating and a bonding layer which are sequentially arranged in a stacked mode; the bonding layer of the composite matrix is attached to a positive plate and / or a negative plate, and after hot pressing, the polymer film layer is removed, so that a solid electrolyte coating is formed on the surface of the positive plate and / or the negative plate. The method is simple and easy to implement and low in cost, the surface density of the solid electrolyte coating can be accurately controlled through cooperation of all the steps, and the structural stability and electrochemical performance of the solid electrolyte coating can be effectively guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of battery technology, and in particular to a preparation method of a solid electrolyte coating, a composite electrode and applications thereof. Background Art

[0002] The traditional liquid battery system is mature, but it is difficult to achieve a significant performance breakthrough. Taking into account both high energy density and intrinsic safety, solid-state all-solid-state lithium-ion batteries will become the battery with the most technologically disruptive potential in the future. Although solid-state batteries have a series of advantages such as high safety, high energy density, and excellent low-temperature performance, the complex production process and high cost limit their industrialization process. Solid-state batteries use solid electrolytes to replace liquid organic electrolytes, and are divided into: semi-solid batteries, quasi-solid-state batteries, and all-solid-state batteries. In view of the great process and technical difficulty of solid-state batteries, and in view of the current technical level and product requirements, the mass production of semi-solid-state batteries has become a general trend. However, in terms of production technology, the coating process of semi-solid electrolyte batteries is an industry problem.

[0003] The solid coating of the current semi-solid-state battery is basically applied on the battery by coating. The disadvantage is that the original positive / negative electrode slurry coating surface density fluctuations on the electrode lead to large fluctuations in the thickness of the electrode, and the thin solid coating applied on the positive and negative electrode leads to the inability to accurately detect the coating surface density and solid coating thickness.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] An object of the present invention is to provide a method for preparing a solid electrolyte coating, which is simple and easy to implement and can accurately control the surface density of the semi-solid electrolyte coating.

[0006] Another object of the present invention is to provide a composite electrode.

[0007] Another object of the present invention is to provide a battery.

[0008] Another object of the present invention is to provide an electrical device.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0010] A method for preparing a solid electrolyte coating comprises the following steps:

[0011] A composite matrix is ​​obtained, wherein the composite matrix includes a polymer film layer, a semi-solid coating and an adhesive layer which are stacked in sequence; the adhesive layer of the composite matrix is ​​bonded to the positive electrode sheet and / or the negative electrode sheet, and after hot pressing, the polymer film layer is removed to form a solid electrolyte coating on the surface of the positive electrode sheet and / or the negative electrode sheet.

[0012] In some embodiments, the method for preparing the composite matrix specifically includes: coating a mixed system formed by a solid electrolyte and a polymer binder on the surface of a polymer film layer to form a first matrix having a semi-solid coating, coating a binder material on the surface of the semi-solid coating to form a bonding layer, and obtaining the composite matrix.

[0013] In some embodiments, the material of the polymer film layer includes at least one of polyvinyl butyral, polypropylene, ceramic decal, vinyl chloride and polystyrene.

[0014] In some embodiments, the adhesive layer includes at least one of a perchloroethylene adhesive, polyvinylidene fluoride, polymethyl methacrylate, and polyacrylic acid.

[0015] In some embodiments, the solid electrolyte includes at least one of an oxide-based electrolyte, a sulfide-based electrolyte, and nanofibers.

[0016] In some embodiments, the polymer binder includes at least one of polyvinylidene fluoride, polymethyl methacrylate, and polyacrylic acid.

[0017] In some embodiments, the mass ratio of the solid electrolyte to the polymer binder is (6-9.5):(0.5-4).

[0018] In some implementations, the hot pressing temperature is 60-500° C., and the hot pressing time is 6000 s.

[0019] A composite electrode comprises a composite positive electrode and / or a composite negative electrode, wherein the composite positive electrode comprises a positive electrode sheet and a solid electrolyte coating located on the surface of the positive electrode sheet, and the composite negative electrode comprises a negative electrode sheet and a solid electrolyte coating located on the surface of the negative electrode sheet, wherein the solid electrolyte coating is prepared by the preparation method of the solid electrolyte coating.

[0020] A battery comprises the composite electrode.

[0021] An electrical device comprises the battery.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] (1) The preparation method of the solid electrolyte coating of the present invention is simple and easy with low cost. The semi-solid coating is first coated on the surface of the composite substrate and then transferred to the surface of the positive electrode sheet and / or the negative electrode sheet to form a solid electrolyte coating. Through the coordination of various steps, the surface density of the solid electrolyte coating can be accurately controlled, and the structural stability and electrochemical performance of the solid electrolyte coating can be effectively guaranteed.

[0024] (2) The composite electrode of the present invention has good structural stability and excellent electrochemical performance.

[0025] (3) The battery of the present invention has excellent structural stability, cycle performance and safety performance. DETAILED DESCRIPTION

[0026] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0027] According to one aspect of the present invention, the present invention relates to a method for preparing a solid electrolyte coating, comprising the following steps:

[0028] A composite matrix is ​​obtained, wherein the composite matrix includes a polymer film layer, a semi-solid coating and an adhesive layer which are stacked in sequence; the adhesive layer of the composite matrix is ​​bonded to the positive electrode sheet and / or the negative electrode sheet, and after hot pressing, the polymer film layer is removed to form a solid electrolyte coating on the surface of the positive electrode sheet and / or the negative electrode sheet.

[0029] The preparation method of the solid electrolyte coating of the present invention is simple, easy and low-cost. The semi-solid coating is first coated on the surface of the polymer film layer (temporary support layer) and then transferred to the surface of the positive electrode sheet and / or the negative electrode sheet to form a solid electrolyte coating. Through the coordination of various steps, the surface density of the solid electrolyte coating can be accurately controlled, and the structural stability and electrochemical properties of the solid electrolyte coating can be effectively guaranteed.

[0030] In some embodiments, the method for preparing the composite matrix specifically includes: coating a mixed system formed by a solid electrolyte and a polymer binder on the surface of a polymer film layer to form a first matrix having a semi-solid coating, coating a binder material on the surface of the semi-solid coating to form a bonding layer, and obtaining the composite matrix.

[0031] In some embodiments, the solid electrolyte includes at least one of an oxide electrolyte, a sulfide electrolyte and nanofibers. In some embodiments, the oxide electrolyte includes one or a combination of zirconium oxide (ZrO2), boehmite (γ-AlOOH), Bi2O3, GeO2, ZnO, Nb2O5, SnO2, SiO2, such as a combination of zirconium oxide and ZnO, a combination of Nb2O5 and SnO2, a combination of GeO2, ZnO and Nb2O5, etc. In some embodiments, the sulfide electrolyte includes a binary sulfide Li2S-P2Q5 and / or a ternary sulfide Li2S-RS2-P2S5, wherein Q is selected from P, Si, Ge or B, and R is selected from Si, Sn, Ge or Al. The nanofiber material includes but is not limited to one or a combination of CNC, CNF, BNC, ECC. The average length of the nanofiber is 0.8-1.5 μm (for example, 0.8 μm, 0.9 μm, 1 μm, 1.5 μm), and the diameter is 0.1-50 μm (for example, 0.1 μm, 0.2 μm, 0.5 μm, 1 μm, 2 μm, 3 μm, etc.).

[0032] In some embodiments, the polymer binder includes at least one of polyvinylidene fluoride, polymethyl methacrylate and polyacrylic acid. The polymer binder can be any one of the above, or a combination of multiple thereof, such as a combination of polyvinylidene fluoride and polymethyl methacrylate, a combination of polymethyl methacrylate and polyacrylic acid, etc. The polymer binder is a commercially available binder.

[0033] In some embodiments, the mass ratio of the solid electrolyte to the polymer binder is (6-9.5):(0.5-4). In some embodiments, the mass ratio of the solid electrolyte to the polymer binder includes but is not limited to 6:4, 6.5:3.5, 7:3, 7.5:2.5, 8:2, 8.5:1.5, 9:1, 9.5:0.5, etc. The solid electrolyte and the polymer binder of the present invention adopt a suitable mass ratio to ensure that the semi-solid electrolyte layer has suitable bonding properties and electrical properties.

[0034] In some embodiments, the solid content of the mixed system formed by the solid electrolyte and the polymer binder is 20% to 90%, for example, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, etc., or any range value between the two; the viscosity of the mixed system is ≥500cp, for example, 500cp, 550cp, 600cp, 650cp, 700cp, 800cp, etc., or any range value between the two.

[0035] In some embodiments, the material of the polymer film layer includes but is not limited to at least one of polyvinyl butyral (PVB), polypropylene, ceramic flower paper, vinyl chloride, and polystyrene, and other resin materials may also be used. Among them, PVB is a condensation product of polyvinyl alcohol and butyraldehyde, and its structure is a white powder with a relative density of 1.08 to 1.10, and it is soluble in methanol, ketones, ethanol, halogenated alkanes, and aromatic solvents. The polymer film layer has suitable strength and can be used as a temporary support layer for the semi-solid coating, and can be better separated from the semi-solid coating in the later stage to ensure the comprehensive performance of the semi-solid coating.

[0036] In some embodiments, the adhesive layer includes at least one of a perchloroethylene adhesive, polyvinylidene fluoride (PVDF), polymethyl methacrylate (PMMA) and polyacrylic acid (PAA). The adhesive layer can be a perchloroethylene adhesive, polyvinylidene fluoride, polymethyl methacrylate or polyacrylic acid, or a combination thereof, such as a combination of a perchloroethylene adhesive and polyvinylidene fluoride, a combination of polyvinylidene fluoride and polymethyl methacrylate, a combination of polymethyl methacrylate and polyacrylic acid, etc.

[0037] In some embodiments, the temperature of the hot pressing is 60 to 500°C, and the time of the hot pressing is 1 to 6000s. In some embodiments, the temperature of the hot pressing includes but is not limited to 60°C, 80°C, 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C, 500°C, etc., or any range between the two. The time of the hot pressing includes but is not limited to 10s, 20s, 30s, 60s, 120s, 240s, 360s, 1200s, 2400s, 3600s, 6000s.

[0038] According to another aspect of the present invention, the present invention also relates to a composite electrode, including a composite positive electrode and / or a composite negative electrode, wherein the composite positive electrode includes a positive electrode sheet and a solid electrolyte coating located on the surface of the positive electrode sheet, and the composite negative electrode includes a negative electrode sheet and a solid electrolyte coating located on the surface of the negative electrode sheet, wherein the solid electrolyte coating is prepared by the method for preparing the solid electrolyte coating.

[0039] The composite pole piece of the invention has excellent structural stability and good electrochemical performance.

[0040] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode material layer located on at least one side of the positive electrode current collector, and the semi-solid electrolyte is located on the surface of the positive electrode material layer. The positive electrode current collector includes conventional aluminum foil, aluminum foil with a porous structure, or composite aluminum foil. Among them, the aluminum foil with a porous structure is obtained by conventional corrosive corrosion. The composite aluminum foil includes a positive electrode base film layer and an aluminum layer located on the surface of the positive electrode base film layer. The aluminum layer can be obtained by evaporation. The material of the positive electrode base film layer includes polyethylene, polypropylene, polyethylene terephthalate, polyvinylidene fluoride, and polyimide. The positive electrode material layer includes a positive electrode active material, a positive electrode binder, and a positive electrode conductive agent. The positive electrode conductive agent includes at least one of conductive carbon black, graphite, carbon nanotubes, carbon fibers, and graphene. The positive electrode binder includes at least one of polyvinylidene fluoride, polyvinyl alcohol, polyurethane, epoxy resin, and polyacrylic acid. The mass ratio of the positive electrode active material, the positive electrode binder and the positive electrode conductive agent is (80-99): (0.5-10): (0.5-10).

[0041] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode material layer located on at least one side of the negative electrode current collector, and the semi-solid electrolyte is located on the surface of the negative electrode material layer. The negative electrode current collector includes at least one of copper foil and composite copper foil. The composite copper foil includes a negative electrode base film layer and a copper layer located on the surface of the negative electrode base film layer, and the negative electrode base film layer includes at least one of polyethylene terephthalate, polyvinylidene fluoride, and polyimide. The negative electrode material layer includes a negative electrode active material, a negative electrode conductor, and a negative electrode binder. The negative electrode active material includes at least one of tin-based materials, graphite, silicon-based materials, and lithium titanate. The negative electrode conductor includes at least one of carbon nanotubes and carbon nanofibers. The negative electrode binder includes at least one of styrene-butadiene rubber, carboxymethyl chitosan, polyacrylic acid, polyacrylamide, polyvinyl alcohol, and polyvinylidene fluoride. The mass ratio of the negative electrode active material, the negative electrode binder, and the negative electrode conductor is (80-99): (0.5-10): (0.5-10).

[0042] According to another aspect of the present invention, the present invention also relates to a battery comprising the composite electrode.

[0043] The battery of the present invention includes a semi-solid battery and a full-solid battery. The full battery includes a composite positive electrode sheet, a composite negative electrode sheet and a separator. The semi-solid battery includes a composite positive electrode sheet, a negative electrode sheet, a separator, an electrolyte, or a cross-over negative electrode sheet, a positive electrode sheet, a separator and an electrolyte, or a composite positive electrode sheet, a composite negative electrode sheet, an electrolyte and a separator. The separator includes at least one of polypropylene (PP), polyethylene (PE) and polyethylene terephthalate (PET).

[0044] The battery of the present invention has excellent structural stability, cycle performance and safety performance.

[0045] According to another aspect of the present invention, the present invention also relates to an electric device, comprising the battery. The electric device of the present invention includes electric vehicles, portable devices and the like.

[0046] The following is further explained in conjunction with specific embodiments.

[0047] Example 1

[0048] A method for preparing a solid electrolyte coating comprises the following steps:

[0049] (a) Obtaining a composite matrix, the composite matrix includes a polymer film layer, a semi-solid coating layer and a bonding layer stacked in sequence; the polymer film layer is made of polyvinyl butyral, and the bonding layer is made of polymethyl methacrylate.

[0050] The specific preparation method of the composite matrix includes: mixing a solid electrolyte and a polymer binder to obtain a high viscosity (580cp) mixed system, wherein the solid electrolyte is zirconium dioxide, the polymer binder is polymethyl methacrylate, and the mass ratio of the solid electrolyte to the polymer binder is 7.5:2.5; coating the mixed system on the surface of the polymer film layer, and the surface density is 0.52mg / cm 2 , with a thickness of 2 μm, to form a first substrate with a semi-solid coating; and then a 1 μm thick bonding layer is prepared on the surface of the semi-solid coating to obtain a composite substrate.

[0051] (b) The bonding layer of the composite substrate is bonded to the positive electrode sheet, the positive electrode sheet includes a positive electrode current collector (aluminum foil) and a positive electrode material layer located on the surface of the positive electrode current collector, the positive electrode material layer includes a positive electrode active material, a positive electrode binder and a positive electrode conductive agent, the mass ratio of which is 94:3:3, and the positive electrode active material is LiNi 0.5 Mn 1.5 O4, the positive electrode binder is polyvinylidene fluoride, and the positive electrode conductive agent is conductive carbon black; and then hot pressing, the hot pressing temperature is 180°C, and the hot pressing time is 30s.

[0052] (c) After hot pressing, the polymer film layer is removed, so that a solid electrolyte coating is formed on the surface of the positive electrode sheet, and the preparation of the solid electrolyte coating is completed, that is, a composite positive electrode sheet is obtained.

[0053] Example 2

[0054] A method for preparing a solid electrolyte coating comprises the following steps:

[0055] (a) Obtaining a composite matrix, the composite matrix includes a polymer film layer, a semi-solid coating layer and a bonding layer stacked in sequence; the polymer film layer is made of polystyrene, and the bonding layer is made of polymethyl methacrylate.

[0056] The specific preparation method of the composite matrix includes: mixing a solid electrolyte and a polymer binder to obtain a high viscosity (600cp) mixed system, wherein the solid electrolyte is boehmite powder, the polymer binder is polyvinylidene fluoride, and the mass ratio of the solid electrolyte to the polymer binder is 8:2; coating the mixed system on the surface of the polymer film layer on the composite matrix, with a surface density of 0.53mg / cm 2 , forming a first substrate having a semi-solid coating; and then preparing a 1 μm thick bonding layer on the surface of the semi-solid coating to obtain a composite substrate.

[0057] (b) The bonding layer in the composite matrix is ​​bonded to the positive electrode sheet, the positive electrode sheet includes a positive electrode current collector (aluminum foil) and a positive electrode material layer located on the surface of the positive electrode current collector, the positive electrode material layer includes a positive electrode active material, a positive electrode binder and a positive electrode conductive agent, the mass ratio of which is 94:3:3, and the positive electrode active material is LiNi 0.5 Mn 1.5 O4, the positive electrode binder is polyvinylidene fluoride, and the positive electrode conductive agent is conductive carbon black; and then hot pressing, the hot pressing temperature is 240°C, and the hot pressing time is 10s.

[0058] (c) After hot pressing, the polymer film layer is removed, so that a solid electrolyte coating is formed on the surface of the positive electrode sheet, and the preparation of the solid electrolyte coating is completed, that is, a composite positive electrode sheet is obtained.

[0059] Example 3

[0060] A method for preparing a solid electrolyte coating comprises the following steps:

[0061] (a) Obtaining a composite matrix, the composite matrix includes a polymer film layer, a semi-solid coating layer and a bonding layer stacked in sequence; the polymer film layer is made of polyvinyl butyral, and the bonding layer is made of polymethyl methacrylate.

[0062] The specific preparation method of the composite matrix includes: mixing a solid electrolyte and a polymer binder to obtain a high viscosity (650cp) mixed system, wherein the solid electrolyte is zirconium dioxide, the polymer binder is polymethyl methacrylate, and the mass ratio of the solid electrolyte to the polymer binder is 7.5:2.5; coating the mixed system on the surface of the polymer film layer on the composite matrix, with a surface density of 0.52mg / cm 2 , forming a first substrate having a semi-solid coating; and then preparing a 1 μm thick bonding layer on the surface of the semi-solid coating to obtain a composite substrate.

[0063] (b) The adhesive layer of the composite matrix is ​​bonded to the negative electrode sheet, the negative electrode sheet includes a negative electrode current collector (copper foil) and a negative electrode material layer located on the surface of the negative electrode current collector, the negative electrode material layer includes a negative electrode active material, a negative electrode binder and a negative electrode conductive agent, the mass ratio of which is 93:3.5:3.5, the negative electrode active material is graphite, the negative electrode binder is polyvinylidene fluoride, and the negative electrode conductive agent is carbon nanotubes; and then hot pressing is performed, the hot pressing temperature is 150°C, and the hot pressing time is 45s.

[0064] (c) After hot pressing, the polymer film layer is removed, so that a solid electrolyte coating is formed on the surface of the negative electrode sheet, and the preparation of the solid electrolyte coating is completed, that is, a composite negative electrode sheet is obtained.

[0065] Example 4

[0066] A method for preparing a solid electrolyte coating comprises the following steps:

[0067] (a) obtaining a composite matrix, wherein the composite matrix comprises a polymer film layer, a semi-solid coating layer, and an adhesive layer which are stacked in sequence; the polymer film layer is made of polyvinyl butyral, and the adhesive layer is made of polyvinylidene fluoride.

[0068] The preparation method of the composite matrix comprises: mixing a solid electrolyte and a polymer binder to obtain a high viscosity (700cp) mixed system, wherein the solid electrolyte is boehmite powder, the polymer binder is polyvinylidene fluoride, and the mass ratio of the solid electrolyte to the polymer binder is 8:2; coating the mixed system on the surface of the polymer film layer on the composite matrix, with a surface density of 0.53mg / cm 2 , forming a first substrate with a semi-solid coating; and then preparing a 1 μm thick bonding layer on the surface of the semi-solid coating to obtain a composite substrate.

[0069] (b) The bonding layer surface of the composite substrate is bonded to the negative electrode sheet, the negative electrode sheet includes a negative electrode current collector (copper foil) and a negative electrode material layer located on the surface of the negative electrode current collector, the negative electrode material layer includes a negative electrode active material, a negative electrode binder and a negative electrode conductive agent, the mass ratio of which is 93:3.5:3.5, the negative electrode active material is graphite, the negative electrode binder is polyvinylidene fluoride, and the negative electrode conductive agent is carbon nanotubes; and then hot pressing is performed, the hot pressing temperature is 190°C, and the hot pressing time is 25s.

[0070] (c) After hot pressing, the polymer film layer is removed, so that a solid electrolyte coating is formed on the surface of the negative electrode sheet, and the preparation of the solid electrolyte coating is completed, that is, a composite negative and positive electrode sheet is obtained.

[0071] Example 5

[0072] A method for preparing a solid electrolyte coating comprises the following steps:

[0073] (a) Obtaining a composite matrix, the composite matrix includes a polymer film layer, a semi-solid coating layer and a bonding layer stacked in sequence; the polymer film layer is made of polyvinyl butyral, and the bonding layer is made of polyvinylidene fluoride and polymethyl methacrylate, with a mass ratio of 2:1.

[0074] The preparation method of the composite matrix specifically includes: mixing a solid electrolyte and a polymer binder to obtain a high viscosity (720cp) mixed system, wherein the solid electrolyte is boehmite powder and zirconium dioxide, the mass ratio of boehmite powder to zirconium dioxide is 1:2, the polymer binder is polyvinylidene fluoride and polymethyl methacrylate, the mass ratio of polyvinylidene fluoride to polymethyl methacrylate is 2:1, and the mass ratio of the solid electrolyte to the polymer binder is 8.5:1.5; coating the mixed system on the surface of the polymer film layer on the composite matrix, the surface density is 0.54mg / cm 2 , forming a first substrate with a semi-solid coating; and then preparing a 1 μm thick bonding layer on the surface of the semi-solid coating to obtain a composite substrate. According to the above method, several composite substrates are obtained.

[0075] (b) Obtaining a composite positive electrode sheet: The two side surfaces of the positive electrode sheet are respectively bonded to the bonding layers of the two composite substrates. The positive electrode sheet includes a positive electrode current collector (aluminum foil) and a positive electrode material layer located on the surface of the positive electrode current collector. The positive electrode material layer includes a positive electrode active material, a positive electrode binder and a positive electrode conductive agent, with a mass ratio of 94:3:3. The positive electrode active material is LiNi 0.5 Mn 1.5 O4, the positive electrode binder is polyvinylidene fluoride, and the positive electrode conductive agent is conductive carbon black; then it is hot pressed, the hot pressing temperature is 220°C, and the hot pressing time is 10s; after hot pressing, the polymer film layer is removed, so that a solid electrolyte coating is formed on the surface of the positive electrode sheet, completing the preparation of the solid electrolyte coating, that is, a composite positive electrode sheet is obtained.

[0076] (c) Obtaining a negative electrode sheet: The two side surfaces of the negative electrode sheet are respectively bonded to the bonding layers of two composite substrates, the negative electrode sheet comprising a negative electrode current collector (copper foil) and a negative electrode material layer located on the surface of the negative electrode current collector, the negative electrode material layer comprising a negative electrode active material, a negative electrode binder and a negative electrode conductive agent, with a mass ratio of 93:3.5:3.5, the negative electrode active material is graphite, the negative electrode binder is polyvinylidene fluoride, and the negative electrode conductive agent is carbon nanotubes; then hot pressing is performed, the hot pressing temperature is 220°C, and the hot pressing time is 10s; after hot pressing, the polymer film layer is removed, so that a solid electrolyte coating is formed on the surface of the negative electrode sheet, and the preparation of the solid electrolyte coating is completed, that is, a composite negative electrode sheet is obtained.

[0077] Example 6

[0078] A method for preparing a solid electrolyte coating comprises the following steps:

[0079] (a) Obtaining a composite matrix, the composite matrix includes a polymer film layer, a semi-solid coating layer and a bonding layer stacked in sequence; the polymer film layer is made of polyvinyl butyral, and the bonding layer is made of polyvinylidene fluoride and polymethyl methacrylate, with a mass ratio of 3:1.

[0080] The preparation method of the composite matrix specifically includes: mixing a solid electrolyte and a polymer binder to obtain a high viscosity (700cp) mixed system, wherein the solid electrolyte is boehmite powder and zirconium dioxide, the mass ratio of boehmite powder to zirconium dioxide is 1:1.5, the polymer binder is polyvinylidene fluoride and polymethyl methacrylate, the mass ratio of polyvinylidene fluoride to polymethyl methacrylate is 3:1, and the mass ratio of the solid electrolyte to the polymer binder is 9:1; coating the mixed system on the surface of the polymer film layer on the composite matrix, the surface density is 0.55mg / cm 2 , forming a first substrate with a semi-solid coating; and then preparing a 1 μm thick bonding layer on the surface of the semi-solid coating to obtain a composite substrate. According to the above method, several composite substrates are obtained.

[0081] (b) Obtaining a composite positive electrode sheet: The two side surfaces of the positive electrode sheet are respectively bonded to the bonding layers of the two composite substrates. The positive electrode sheet includes a positive electrode current collector (aluminum foil) and a positive electrode material layer located on the surface of the positive electrode current collector. The positive electrode material layer includes a positive electrode active material, a positive electrode binder and a positive electrode conductive agent, with a mass ratio of 94:3:3. The positive electrode active material is LiNi 0.5 Mn 1.5 O4, the positive electrode binder is polyvinylidene fluoride, and the positive electrode conductive agent is conductive carbon black; then it is hot pressed, the hot pressing temperature is 175°C, and the hot pressing time is 33s; after hot pressing, the polymer film layer is removed, and a solid electrolyte coating is formed on the surface of the positive electrode sheet, completing the preparation of the solid electrolyte coating, that is, a composite positive electrode sheet is obtained.

[0082] (c) Obtaining a negative electrode sheet: The two side surfaces of the negative electrode sheet are respectively bonded to the bonding layers of two composite substrates, the negative electrode sheet comprising a negative electrode current collector (copper foil) and a negative electrode material layer located on the surface of the negative electrode current collector, the negative electrode material layer comprising a negative electrode active material, a negative electrode binder and a negative electrode conductive agent, the mass ratio of which is 93:3.5:3.5, the negative electrode active material is graphite, the negative electrode binder is polyvinylidene fluoride, and the negative electrode conductive agent is carbon nanotubes; then hot pressing is performed, the hot pressing temperature is 160°C, and the hot pressing time is 40s; after hot pressing, the polymer film layer is removed, so that a solid electrolyte coating is formed on the surface of the negative electrode sheet, and the preparation of the solid electrolyte coating is completed, that is, a composite negative electrode sheet is obtained.

[0083] Example 7

[0084] A method for preparing a battery comprises the following steps:

[0085] The composite positive electrode sheet and negative electrode sheet obtained in Example 1, a separator and an electrolyte are assembled to obtain a battery. The separator is PE, and the separator is located between any adjacent positive electrode sheets and negative electrode sheets.

[0086] The negative electrode sheet includes a negative electrode current collector (copper foil) and a negative electrode material layer located on the surface of the negative electrode current collector. The negative electrode material layer includes a negative electrode active material, a negative electrode binder and a negative electrode conductive agent in a mass ratio of 93:3.5:3.5. The negative electrode active material is graphite, the negative electrode binder is polyvinylidene fluoride, and the negative electrode conductive agent is carbon nanotubes.

[0087] The electrolyte solvent includes, by mass percentage, 85% solvent (EC+DMC+EMC, volume ratio of 1:1:1), 10% lithium salt LiPF6 and 5% additive (vinylene carbonate).

[0088] Example 8

[0089] A method for preparing a battery comprises the following steps:

[0090] The composite positive electrode sheet and negative electrode sheet obtained in Example 2, a separator and an electrolyte are assembled to obtain a battery. The separator is PE, and the separator is located between any adjacent composite positive electrode sheet and negative electrode sheet.

[0091] The negative electrode sheet includes a negative electrode current collector (copper foil) and a negative electrode material layer located on the surface of the negative electrode current collector. The negative electrode material layer includes a negative electrode active material, a negative electrode binder and a negative electrode conductive agent in a mass ratio of 93:3.5:3.5. The negative electrode active material is graphite, the negative electrode binder is polyvinylidene fluoride, and the negative electrode conductive agent is carbon nanotubes.

[0092] The electrolyte solvent includes, by mass percentage, 85% solvent (EC+DMC+EMC, volume ratio of 1:1:1), 10% lithium salt LiPF6 and 5% additive (vinylene carbonate).

[0093] Example 9

[0094] A method for preparing a battery comprises the following steps:

[0095] The composite negative electrode sheet and positive electrode sheet obtained in Example 3, a separator and an electrolyte are assembled to obtain a battery. The separator is PE, and the separator is located between any adjacent positive electrode sheets and composite negative electrode sheets.

[0096] The positive electrode sheet includes a positive electrode current collector (aluminum foil) and a positive electrode material layer located on the surface of the positive electrode current collector. The positive electrode material layer includes a positive electrode active material, a positive electrode binder and a positive electrode conductive agent, with a mass ratio of 94:3:3. The positive electrode active material is LiNi 0.5 Mn 1.5 O4, the positive electrode binder is polyvinylidene fluoride, and the positive electrode conductive agent is conductive carbon black.

[0097] The electrolyte solvent includes, by mass percentage, 85% solvent (EC+DMC+EMC, volume ratio of 1:1:1), 10% lithium salt LiPF6 and 5% additive (vinylene carbonate).

[0098] Example 10

[0099] A method for preparing a battery comprises the following steps:

[0100] The composite negative electrode sheet and positive electrode sheet obtained in Example 4, a separator and an electrolyte are assembled to obtain a battery. The separator is PE, and the separator is located between any adjacent positive electrode sheets and composite negative electrode sheets.

[0101] The positive electrode sheet includes a positive electrode current collector (aluminum foil) and a positive electrode material layer located on the surface of the positive electrode current collector. The positive electrode material layer includes a positive electrode active material, a positive electrode binder and a positive electrode conductive agent, with a mass ratio of 94:3:3. The positive electrode active material is LiNi 0.5 Mn 1.5 O4, the positive electrode binder is polyvinylidene fluoride, and the positive electrode conductive agent is conductive carbon black.

[0102] The electrolyte solvent includes, by mass percentage, 85% solvent (EC+DMC+EMC, volume ratio of 1:1:1), 10% lithium salt LiPF6 and 5% additive (vinylene carbonate).

[0103] Embodiment 11

[0104] The composite positive electrode sheet and the composite negative electrode sheet obtained in Example 5 are assembled into a battery with a separator and an electrolyte. The separator is PET, and the separator is located between any adjacent positive electrode sheets and negative electrode sheets.

[0105] The electrolyte solvent includes, by mass percentage, 85% solvent (EC+DMC+EMC, volume ratio of 1:1:1), 10% lithium salt LiPF6 and 5% additive (vinylene carbonate).

[0106] Example 12

[0107] A method for preparing a battery comprises the following steps:

[0108] The composite positive electrode sheet and the composite negative electrode sheet obtained in Example 6 are assembled into a battery with a separator and an electrolyte. The separator is PET, and the separator is located between any adjacent positive electrode sheets and negative electrode sheets.

[0109] The electrolyte solvent includes, by mass percentage, 85% solvent (EC+DMC+EMC, volume ratio of 1:1:1), 10% lithium salt LiPF6 and 5% additive (vinylene carbonate).

[0110] Experimental example

[0111] In order to verify the improvement effect of semi-solid state batteries in performance and safety, cycle test, hot box test, ARC test and shallow puncture test were carried out on the relevant batteries. The test results are shown in Table 1.

[0112] Cycle test: 1C / 1C, 100% DOD cycle 1000cls.

[0113] 140℃ hot box test: 1C constant current and constant voltage fully charged to 4.2V (0.05C cut-off); let stand for 1h; heat in the test box to 140min, and keep at 140℃ for 30min, then observe for 1h.

[0114] Shallow puncture test: 1C constant current and constant voltage fully charged to 4.2V (0.05C cut-off); let stand for 1 hour; make a slit on the large surface of the battery and protect it with aluminum-plastic film. Use a steel needle with a diameter of 1mm and an angle of 30° to puncture the aluminum-plastic film. Stop puncturing when the voltage fluctuates significantly. After standing for 3 hours, disassemble the battery cell.

[0115] Table 1 Test results

[0116]

[0117]

[0118] As can be seen from Table 1, the thermal runaway time of the semi-solid-state battery obtained by the method of the present invention is prolonged, and the puncture resistance is increased when shallowly punctured, indicating that the semi-solid-state battery obtained by the method of the present invention has excellent electrochemical properties and safety performance.

[0119] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a solid electrolyte coating, characterized in that: The following steps are involved: Obtaining a composite matrix, wherein the composite matrix comprises a polymer film layer, a semi-solid coating layer and a bonding layer stacked in sequence; The bonding layer of the composite matrix is ​​bonded to the positive electrode sheet and / or the negative electrode sheet, and after hot pressing, the polymer film layer is removed to form a solid electrolyte coating on the surface of the positive electrode sheet and / or the negative electrode sheet.

2. The method for preparing a solid electrolyte coating according to claim 1, characterized in that: The preparation method of the composite matrix specifically includes: coating a mixed system formed by a solid electrolyte and a polymer binder on the surface of a polymer film layer to form a first matrix with a semi-solid coating, coating a binder material on the surface of the semi-solid coating to form a bonding layer, and obtaining the composite matrix.

3. The method for preparing a solid electrolyte coating according to claim 1, characterized in that: The material of the polymer film layer includes at least one of polyvinyl butyral, polypropylene, ceramic flower paper, vinyl chloride and polystyrene.

4. The method for preparing a solid electrolyte coating according to claim 1, characterized in that: The adhesive layer includes at least one of perchlorethylene adhesive, polyvinylidene fluoride, polymethyl methacrylate and polyacrylic acid.

5. The method for preparing a solid electrolyte coating according to claim 2, characterized in that: The solid electrolyte includes at least one of an oxide electrolyte, a sulfide electrolyte and nanofibers; And / or, the polymer binder includes at least one of polyvinylidene fluoride, polymethyl methacrylate and polyacrylic acid.

6. The method for preparing a solid electrolyte coating according to claim 2, characterized in that: The mass ratio of the solid electrolyte to the polymer binder is (6-9.5):(0.5-4).

7. The method for preparing a solid electrolyte coating according to claim 1, characterized in that: The temperature of the hot pressing is 60-500° C., and the time of the hot pressing is 1-6000 s.

8. A composite electrode, characterized in that: It comprises a composite positive electrode and / or a composite negative electrode, wherein the composite positive electrode comprises a positive electrode sheet and a solid electrolyte coating located on the surface of the positive electrode sheet, and the composite negative electrode comprises a negative electrode sheet and a solid electrolyte coating located on the surface of the negative electrode sheet, wherein the solid electrolyte coating is prepared by the preparation method of the solid electrolyte coating according to any one of claims 1 to 7.

9. A battery, characterized in that: Comprising the composite electrode as claimed in claim 8.

10. An electrical device, characterized in that: A battery comprising the battery of claim 9.

Citation Information

Patent Citations

  • Composite electrolyte membrane, preparation method and application thereof, and solid-state lithium battery

    CN112838266A

  • Electrolyte composite membrane of solid-state battery, preparation method of electrolyte composite membrane and solid-state battery

    CN114865075A

  • Solid electrolyte membrane, preparation method of solid electrolyte membrane, all-solid-state battery and manufacturing method of all-solid-state battery

    CN115441047A

  • Preparation method of pole piece, positive pole piece and lithium ion battery

    CN115714164A

  • Membrane-electrode assembly manufacturing method and membrane-electrode assembly

    JP2016219180A

Cited By

  • Preparation method of rare earth composite solid electrolyte coating material

    CN121790499A

  • A method for preparing a rare earth composite solid electrolyte coating material

    CN121790499B